ANTIOXIDANT THERAPY IN THE ELDERLY WITH TINNITUS: SYSTEMATICS REVIEW - Syahputra, Febrian (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Tinnitus is one of the most prevalent and annoying disorders that affect the ear and the auditory system. It is one of the most important symptoms in neurootology, along with hearing loss, vertigo, dizziness, and nausea. It can cause a variety of somatic and psychological disorders that interfere with a person's quality of life. There is a correlation between oxidative stress and tinnitus. Hair cell apoptosis, cochlear degeneration, alterations to supporting structures and stria vascularis, changes to the nerve fibers of the acoustic nerve, irregular neuronal activity in the auditory pathway, and malfunction in the central cortex are all possible outcomes of oxidative stress. Animal models of aging, noise damage, and ototoxicity have been used to investigate the relationship between oxidative stress and the death of hair cells. Antioxidants are substances that can take on a wide variety of chemical structures, but they are categorized as a single class because they share the ability to neutralize the effects of highly reactive and potentially damaging free radicals. These radicals are produced when foods undergo the necessary oxidation reactions that are a natural part of the digestion process. Antioxidant supplementation with vitamins, minerals, phytochemicals, and alpha-lipoic acid (ALA) might have therapeutic effects on tinnitus by reducing the subjective discomfort and the level of severity caused by the ringing in the ears.